Anemonin Attenuates RANKL-Induced Osteoclastogenesis and Ameliorates LPS-Induced Inflammatory Bone Loss in Mice via Modulation of NFATc1 - Hou, Huanhuan; Peng, Qisheng; Wang, Shaoming; Zhang, Yuxin; Cao, Jinjin; Deng, Yuming; Wang, Yingjian; Sun, Wan-chun; Wang, Hong-bing (Frontiers in Pharmacology, 2020)
Osteoporosis is a metabolic bone disease characterized by insufficient osteoblastic function and/or excessive osteoclastic activity. One promising strategy for treating osteoporosis is inhibiting excessive osteoclast resorbing activity. Previous studies have revealed that anemonin (ANE), isolated from various types of Chinese natural herbs, has anti-inflammatory and anti-oxidative properties. However, whether ANE regulates osteoclastogenesis is unknown. This study aimed to investigate the potential effect of ANE on osteoclastogenesis and inflammatory bone loss in mice. In in vitro studies, ANE suppressed RANKL-stimulated osteoclast differentiation and function by downregulating the expression of osteoclast master transcriptor NFATc1, as well as its upstream transcriptor c-Fos, by decreasing NF-κB and ERK1/2 signaling. Interestingly, ANE did not change the phosphorylation and degradation of IκB-α and activation of JNK and p38 MAPKs. However, ANE repressed the phosphorylation of MSK-1 which is the downstream target of ERK1/2 and p38 MAPK and can phosphorylate NF-κB p65 subunit. These results implicated that ANE might suppress NF-κB activity via modulation of ERK1/2 mediated NF-κB phosphorylation. In addition, ANE directly suppressed NFATc1 transcription by inhibiting Blimp-1 expression, and the subsequent enhancement of the expression of NFATc1 negative regulators, Bcl-6 and IRF-8. Moreover, in vivo studies were conducted using an LPS-induced inflammatory bone loss mice model. Micro-CT and histology analysis showed that ANE treatment significantly improved trabecular bone parameters and bone destruction. These data indicate that ANE can attenuate RANKL-induced osteoclastogenesis and ameliorate LPS-induced inflammatory bone loss in mice through modulation of NFATc1 via ERK1/2-mediated NF-κB phosphorylation and Blimp1 signal pathways. ANE may provide new treatment options for osteoclast-related diseases.